(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The Shalakya Tantra, being a speciality which deals about the Uttamanga where Sarvendriyas are located has a very significant role in contribution for health. Shalakya Tantra is among the eight branches of Ayurveda which deals with the diseases above Jatru region i.e., the disease of eye, ear, nose, throat, head. The prime contributions are of Acharya Nimi, Acharya Sushruta, Acharya Vagbhata for Shalakya tantra. My present work is planned and aimed at critically appraising any additional contributions to Shalakya Tantra made by Acharya Harita from his text Harita Samhita. After compiling and critically appraising, many new nomenclatures were added by Acharya Harita. He also added description of new disease entities to the existing ones example Bhrudosha, Netrapushpa which opens new horizons to understand Shalakya related disorders in a new light and to develop novel treatment protocols. He has mentioned Bindutraya, and Shadbindu taila with new combinations. This will help us to explore the clinical success in many such diseases. Harita Samhita was written by Acharya Harita during 6-7 AD based on the conversation between his Guru Acharya Punarvasu and himself. All additional contributions from Acharya Harita are compiled in a reader friendly version with proper tabular representations.